Pathogenic Lifestyles of E. coli Pathotypes in a Standardized Epithelial Cell Model Influence Inflammatory Signaling Pathways and Cytokines Secretion - Sanchez-Villamil, Javier; Tapia-Pastrana, Gabriela; Navarro-Garcia, Fernando (Frontiers in Cellular and Infection Microbiology, 2016)
Inflammatory response is key for the host defense against diarrheagenic E. coli and contributes to the pathogenesis of the disease but there is not a comparative study among different diarrheagenic pathotypes. We analyzed the inflammatory response induced by five diarrheagenic pathotypes in a HT-29 cell infection model. The model was unified to reproduce the pathogenesis of each pathotype. To compare the inflammatory responses we evaluated: (i) nuclear NF-κB and ERK1/2 translocation by confocal microscopy; (ii) kinetics of activation by each pathway detecting p65 and ERK1/2 phosphorylation by Western blotting; (iii) pathways modulation through bacterial infections with or without co-stimulation with TNF-α or EGF; (iv) cytokine profile induced by each pathotype with and without inhibitors of each pathway. EHEC but mainly EPEC inhibited translocation and activation of p65 and ERK1/2 pathways, as well as cytokines secretion; inhibition of p65 and ERK1/2 phosphorylation prevailed in the presence of TNF-α and EGF, respectively. Intracellular strains, EIEC/S. flexneri, caused a strong translocation, activation and cytokines secretion but they could not inhibit TNF-α and EGF stimulation. ETEC and mainly EAEC caused a moderate translocation, but a differential activation, and high cytokines secretion; interestingly TNF-α and EGF stimulation did no modify p65 and ERK1/2 activation. The use of inhibitors of NF-κB and/or ERK1/2 showed that NF-κB is crucial for cytokine induction by the different pathotypes; only partially depended on ERK1/2 activation. Thus, in spite of their differences, the pathotypes can also be divided in three groups according to their inflammatory response as those (i) that inject effectors to cause A/E lesion, which are able to inhibit NF-κB and ERK1/2 pathways, and cytokine secretion; (ii) with fimbrial adherence and toxin secretion with a moderate inhibition of both pathways but high cytokines secretion through autocrine cytokine regulation; and (iii) the intracellular bacteria that induce the highest pathways activation and cytokines secretion by using different activation mechanisms. This study provides a comprehensive analysis of how the different pathogenesis schemes of E. coli pathotypes manipulate inflammatory signaling pathways, which leads to a specific proinflammatory cytokine secretion in a cell model infection that reproduce the hallmarks of infection of each pathotype.